SAT0393 Health Related Quality of Life in Rheumatoid Arthritis and Systemic Lupus Erythematosus Patients in Switzerland: Not the Same Impact!. (9th June 2015) - Chaigne, B.; Finckh, A.; Neto, D.; Alpizar Rodriguez, D.; Ribi, C.; Chizzolini, C.
Abstract : Background: Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are chronic systemic autoimmune diseases with different pathogenesis, that share susceptibility genes and both diseases can alter patients' quality of life (1, 2). Quality of life has imposed itself as an important outcome measure and the assessment of health related quality of life (HRQoL) is included in therapeutic goals and evaluation of novel treatments (3, 4). Objectives: To compare health-related quality of life (HRQoL) in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) in Switzerland. Methods: The primary outcome of this study was to assess and compare HRQoL in patients with SLE and RA. In this analysis, we included patients from the multicenter Swiss SLE cohort study (SSCS) and age and sex matched patients from the multicenter Swiss Clinical Quality Management Program for Rheumatoid Arthritis (SCQM) databases that were assessed for HRQoL using the SF-36 physical component scale (PCS) and mental component scale (MCS). Marginal longitudinal regression was used to identify and test predictive factors of HRQoL in the two diseases. Finally, analysis of variance was used to test HRQoL difference between both groups. Results: A total of 267 patients with SLE and 267 matched patients with RA were analysed. The median [Interquartile range (IQR)] MCS and PCS scores were 46.9 [35.5-54.3] and 40.8 [33.5-47.1] in SLE and 48.8 [37.6-56.7] and 34.7 [26.8-43.0] in RA, respectively. Thus, the MCS was significantly lower in SLE patients (p=0.04), while the PCS was significantly lower in RA patients (p<0.001). Such differences were confirmed in the longitudinal model that showed a significant improvement on PCS in RA patients during the time of follow-up. Conclusions: While SLE and RA both affect HRQoL, patients with SLE have lower MCS whereas patients with RA have lower PCS. These alterations persist after one year of follow-up and indicate fundamental differences in the impact of disease in these two populations. References: Lisnevskaia L, Murphy G, Isenberg D. Systemic lupus erythematosus. Lancet. 2014 May 29; Scott DL, Wolfe F, Huizinga TWJ. Rheumatoid arthritis. Lancet. 2010 Sep 25;376(9746):1094–108. Strand V, Levy RA, Cervera R, Petri MA, Birch H, Freimuth WW, et al. Improvements in health-related quality of life with belimumab, a B-lymphocyte stimulator-specific inhibitor, in patients with autoantibody-positive systemic lupus erythematosus from the randomised controlled BLISS trials. Ann Rheum Dis. 2014 May;73(5):838–44. Bingham CO, Weinblatt M, Han C, Gathany TA, Kim L, Lo KH, et al. The effect of intravenous golimumab on health-related quality of life in rheumatoid arthritis: 24-week results of the phase III GO-FURTHER trial. J Rheumatol. 2014 Jun;41(6):1067–76 Disclosure of Interest: None declared